Effect of community treatment initiative on antiretroviral therapy uptake among linkage-resistant people living with HIV in Northern Nigeria. (October 2019) - Katbi, Moses; Adegboye, Adeoye Ayodeji; Bello, Maryam; Gumel, Aliyu Gambo; Adedoyin, Adefisayo; Yunusa, Fadimatu; Kayode, Gbenga; Yusuf, Oche Baba; Anjorin, Atinuke; Abone, Chizoba Geraldine; Ukaere, Amalachukwu; Ekong, Ernest; et al.
Highlights: Inadequate identification of new HIV cases is a global HIV burden. Linkage-resistant HIV clients belong to a high-risk population group that must be reached in order to control the HIV epidemic. Community treatment initiative through community health workers help to reach these clients and increase the chances of enrolling this high-risk population into HIV care and treatment. Retention in care and eventually virological suppression is needed if the HIV epidemic is to potentially end. Abstract: Background: Community Treatment Initiative (CTI) was developed in northern Nigeria as an intervention to link a cohort of people living with HIV (PLHIV) who refused antiretroviral treatment through a conventional linkage method to care and treatment. The CTI attempted to take treatment to PLHIV in the community. Methods: This was a non-control interventional study that evaluated the proportion of linkage-resistant PLHIV linked to treatment through the CTI in nine geographical areas. Data were collected between October and December 2015. Linkage-resistant PLHIV were identified and linked to treatment using the CTI. Data were analyzed using Excel and IBM SPSS version 20.0. The simple proportion was used to estimate the linkage-resistant PLHIV who were eventually linked and retained in care and who ultimately achieved virological suppression (viral load <1000 copies/ml). The Chi-square test was used and the level of significance set at a p -value of <0.05. Results: An estimated 541 (20%) PLHIV (239 (44.2%) male, 302 (55.8%) female) seen from October to December 2015 refused linkage to treatment. This was statistically significant at a p -value of <0.0001. Three hundred and seventy-seven (69.7%) of the PLHIV who refused linkage to treatment eventually accepted treatment using an alternative community treatment method; this was significant ( p < 0.0001). The 6-month retention rate for PLHIV who accepted the alternative treatment method was 88.1% ( n = 332); this was significant ( p < 0.0001). Seventy-eight percent of those retained in care attained virological suppression. Conclusions: The CTI improved linkage to care and treatment for a cohort of linkage-resistant PLHIV. Focus on this cohort of linkage-resistant positive clients is required to achieve HIV epidemic control.